KAJIAN KUALITAS RUANG PUBLIK PADA ALUN-ALUN GRESIK - Akhmad Ilyas Arifudin; Franciscus Immanuel Mintardjo; Rizal Jannatan Firdaus; Adibah Nurul Yunisya (Ide dan Dialog Desain Indonesia (Idealog), 2021)
The square is a public space which is a center of a crowd in a city. Public spaces are said to have good quality if they meet the following criteria: imageability, enclosure, human scale, transparency and complexity. In the city of Gresik, there is a square which is becoming residents main space in conducting social interaction. But in its development, Gresik Square underwent a revitalization into an Islamic Center. The image of Alun-alun Gresik which was originally an open area slowly began to change due to the revitalization. The purpose of this study was to study the quality of Gresik Square as a public space based on direct observations and user perceptions. In this study, qualitative methodology is used which is conducted through direct observation at the location and questionnaires filled out by people who have visited Gresik Square. The analysis of the quality criteria of Gresik Square is presented in a qualitative descriptive manner which is supported by the opinion of the respondents. The results of the analysis show that the Gresik Square has a public space quality that is not good enough because it does not meet the quality criteria for public space. Keywords : Alun-alun, Image, Public Space